TURKISH LAICISM IN INDONESIA’S NEWSPAPERS (1920-1940) AND ITS INFLUENCE ON INDONESIAN SECULARISTS AND MUSLIMS THOUGHTS (JOURNAL OF INDONESIAN ISLAM, 2021)
The Republic of Turkey was established in 1923 after the Treaty of Sevres and Lausanne were ratified by the Turkish nationalists led by Mustafa Kamal. This establishment has marked the beginning of a new era in the political, social, economic, and cultural lives of Turks. The main concern for Turkish statesmen was laicism. The policy has a significant effect on the global world, especially for the Dutch Indies. The purpose of this article is to provide a critical analysis of the roles of Indonesian-language newspapers in informing Dutch Indies citizens about Turkey's secularization process and how newspapers served as the primary medium for disseminating information about Turkey. Through newspapers, Muslims from Nusantara (the archipelago) expressed their views on the Turks’ secularisation efforts. This study employed a historical method using contemporary Indonesian-language newspapers from the National Library of the Republic of Indonesia. The news of Turkey’s secularisation had a significant impact on the thoughts of Indonesian secularists and Muslims in laying the nation’s foundation in the 1940s.